Interprofessional communication from the organizational culture of nursing care - Concepción Lucas García; Carmen Isabel Gómez García; Josefa María Antón Hurtado (Universidad de Alicante, 2012)
Introduction: Good communication between health professionals is recognized as essential for proper patient care, but many authors claim that it remains one of the unfinished business of healthcare organizations. Objectives: To explore the expectations and ideas nurses have about interprofessional communication in an intensive care unit in a district hospital and establish its relationship to cultural, organizational and personal. Material and methods: This is a descriptive qualitative methodology, using data collection in-depth semi-structured interviews. Results: After content analysis identified two categories: expressions of the reality of the communicative interactions between professionals and professional expectations and their proposals for improvement. Conclusions and Discussion: Each health profession has a different culture that makes each one has its own values and disciplinary point of view of the needs of the patient but also different styles of communication. It is important to recognize that effective communication is complex and multifactorial, but the leaders should take the concern and interest expressed by professionals to promote iniciatives for the exchange and collaboration.